The exponentiated Akash distribution with properties and applications - عبد الرحيم بسيوني; نصر رشوان (Maǧallaẗ Al-Buḥūṯ Al-Mālīyyaẗ wa Al-Tiğāriyyaẗ, 2021)
In this study, a new two-parameter lifetime distribution named the exponentiated Akash distribution is introduced and studied. Akash distribution is considered an extension of the lindly distribution and can be easily expressed as a mixture of an exponential distribution with scale parameter (θ) and a gamma distribution with shape parameter equal 3 and scale parameter θ . The reliability (survival) function, hazard rate function (also known as the failure rate function), the reversed hazard rate and the cumulative hazard rate function of the new distribution are obtained. Some statistical properties of the exponentiated Akash distribution such as the moments, moment generating function, order statistics, Renyi entropy and quantile function are derived. The method of maximum likelihood is used to estimate the unknown parameters of this distribution. Finally, the performance of this new distribution is examined using some real life data sets to show its flexibility and better goodness of fit as compared with other lifetime distributions such as Akash and exponential based on the Akaike information criterion.